ELEMENTS OF TAXATION AND THEIR ECONOMIC EFFECTS - Mariana PERȚEA (Annals of the University of Oradea: Economic Science)
This paper analyzes taxation and its elements and aspects of Romania’s evolution. Direct and indirect taxes are fundamental elements of the Romanian tax system and own resources that the state can obtain. The article also delves into the future perspectives of taxation and their potential impact on Romania, providing a comprehensive understanding of this evolving landscape.Taxation represents a central aspect of economic policy, having a crucial role in financing public expenditures and influencing economic agents economic behavior. The main elements of taxation include taxes, duties, and social contributions. Taxation is an essential tool of economic policy, financing public expenditure and influencing economic behavior. Through its various elements and effects, taxation contributes to the achievement of the economic and social objectives of a state.